Fabrication of Bilayer Nanofibrous-Hydrogel Scaffold from Bacterial Cellulose, PVA, and Gelatin as Advanced Dressing for Wound Healing and Soft Tissue Engineering - Khan, Rawaiz; Aslam Khan, Muhammad Umar; Stojanović, Goran M.; Javed, Aneela; Haider, Sajjad; Abd Razak, Saiful Izwan (ACS omega, 2024)
Tissue engineering is currently one of the fastest-growing areas of engineering, requiring the fabrication of advanced and multifunctional materials that can be used as scaffolds or dressings for tissue regeneration. In this work, we report a bilayer material prepared by electrospinning a hybrid material of poly(vinyl alcohol) (PVA) and bacterial cellulose (BC NFs) (top layer) over a highly interconnected porous 3D gelatin-PVA hydrogel obtained by a freeze-drying process (bottom layer). The techniques were combined to produce an advanced material with synergistic effects on the physical and biological properties of the two materials. The bilayer material was characterized using Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and a water contact measurement system (WCMS). Studies on swelling, degradability, porosity, drug release, cellular and antibacterial activities were performed using standardized procedures and assays. FTIR confirmed cross-linking of both the top and bottom layers, and SEM showed porous structure for the bottom layer, random deposition of NFs on the surface, and aligned NFs in the cross section. The water contact angle (WCA) showed a hydrophilic surface for the bilayer material. Swelling analysis showed high swelling, and degradation analysis showed good stability. The bilayer material released Ag-sulfadiazine in a sustained and controlled manner and showed good antibacterial activities against severe disease-causing gram + ive and −ive (Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa) bacterial strains. In vitro biological studies were performed on fibroblasts (3T3) and human embryonic kidneys (HEK-293), which showed desirable cell viability, proliferation, and adhesion to the bilayer. Thus, the synergistic effect of NFs and the hydrogel resulted in a potential wound dressing material for wound healing and soft tissue engineering.